HEALTH EDUCATION ABOUT THE DANGERS OF OUT-OF-WEDLOCK PREGNANCY AMONG ADOLESCENTS - Putra, Kusuma Wijaya Ridi; Niah, Najah Soraya; Puspita, Sylvie; Zatihulwani, Eliza Zihni; Rustanti, Elly; Ana, Karisma Dwi (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
The modern era like now is supported by increasingly sophisticated technology, everyone can access various information from various parts of the world easily. One of them is the desire to try new things that are prohibited based on their norms or values, but they are curious to know and try them. Most societies still have the paradigm that sex education is something vulgar and adolescents should learn from their environment. The views of society in general reveal that for the average parent, talking about sex and sexuality is a new understanding. The aim of carrying out this community service activity is to teach adolescents about the dangers of pregnancy outside of marriage among adolescents. This community service activity was carried out at the Mancar Village Hall, Peterongan District, Jombang Regency on November 11, 2023 by providing health education and guidance to adolescents regarding the dangers of out-of-wedlock pregnancy among adolescents. This activity was attended by 30 adolescents and accompanied by health cadres. The activity was carried out well. Based on the results of the evaluation carried out using a questionnaire, it was found that 9 adolescents had a good level of knowledge during the pretest and this increased to 14 adolescents during the posttest. By increasing understanding regarding the dangers of pregnancy outside of marriage, it is hoped that adolescents will be able to prevent themselves from becoming pregnant outside of marriage.